Presence of hazardous chemical elements in low-cost children's toys: A risk to their development in early childhood - Reem A. Alsaigh; Hayat S. Althobaiti; Naushad Ahmad; Mohammad Rizwan Khan (Journal of King Saud University: Science, 2024)
Objectives: The objectives of the current study was to study the presence of hazardous chemical elements (Ba138, Cd111, Cr52, Pb208, As75, Co59, Cu63, Mn55, Ni60, Se82, Sr88, Zn66 and Hg202) in low-cost children's toys, and the effect of color types on chemical element concentrations. Methods: Children's toy samples were analyzed using microwave digestion and inductively coupled plasma/mass spectrometry (ICP/MS) method. Samples were prepared into small pieces, and 500 mg of homogenized sample was used for digestion by means of digesting regents HNO3 (65 %, 5 mL) and H2O2 (35 %, 1 mL). During the digestion process, the pressure was held constant at 90 bar and the temperature, hold time, and power were varied 150–170-40° C, 10–30-5 min, 70–90-0 %, respectively. The main operating conditions of ICP/MS were: spray chamber temperature (−20 °C), RF Power (1450 W), nebulizer gas flow (0.9 L/min), auxiliary gas flow (0.8 L/min) and plasma gas flow (14.85 L/min). Samples and blanks were analyzed for 30 s and system was operated in standard mode. Results: The excellent method performance was achieved in terms of limit of detection (LOD, 0.001–14.89 µg/L); limit of quantification (LOQ, 0.003–45.12 µg/L); correlation coefficient (R2, 0.975–0.999) with relative standard deviation values (RSD, 0.70–4.98 %). Chemical elements were found in all the toys (0.01–742.72 ng/g) except sample S2 where only Hg202 was found (0.01 ng/g). Outcomes revealed that the Hg202 was present at a very low level (0.01 ng/g) while Zn66 was present at very high level (742.72 ng/g). Furthermore, the toys contamination was also found to be color-specific, with significant amount of chemical elements was found in black type car sample (S5, 946.98 ng/g) whereas other color type samples constitute lower amounts (0.001–210.53 ng/g). Low-cost toys designed for children's use are found to contain chemical elements that should be addressed in the course of action. As a result of exposure to high amounts of chemical elements in toys, children have a high chance of developing cancer.